Selective Photoinactivation of Methicillin‐Resistant Staphylococcus aureus by Highly Positively Charged RuII Complexes - Feng, Yang; Sun, Wei‐Ze; Wang, Xue‐Song; Zhou, Qian‐Xiong (Chemistry : a European journal, 2019)
Ruthenium(II) polypyridyl complexes featuring peripheral quaternary ammonium structures were found to be able to selectively inactivate Gram‐positive Staphylococcus aureus (S. aureus), including methicillin‐resistant S. aureus (MRSA) upon visible light irradiation, but have low phototoxicity toward 293T cells, L02 cells and lack hemolysis toward rabbit red blood cells (RBC), exhibiting promising potential as a novel type of antimicrobial photodynamic therapy (aPDT) agents. Ruthenium(II) polypyridyl complexes featuring peripheral quaternary ammonium structures were found to be able to selectively inactivate MRSA but have extremely low cytotoxicity toward mammalian cells upon visible light irradiation.